2017
DOI: 10.1371/journal.pone.0171974
|View full text |Cite
|
Sign up to set email alerts
|

Secondary-structure prediction revisited: Theoretical β-sheet propensity and coil propensity represent structures of amyloids and aid in elucidating phenomena involved in interspecies transmission of prions

Abstract: Prions are unique infectious agents, consisting solely of abnormally-folded prion protein (PrPSc). However, they possess virus-like features, including strain diversity, the ability to adapt to new hosts and to be altered evolutionarily. Because prions lack genetic material (DNA and RNA), these biological phenomena have been attributed to the structural properties of PrPSc. Therefore, many structural models of the structure of PrPSc have been proposed based on the limited structural information available, rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…To compare influences of hydrophobic amino acids on the local structures of αSyn amyloids, we introduced Met substitution at residues 61 (E61M) and 84 (G84M), where we previously investigated influences of Ile substitutions [24]. We first estimated alteration to intrinsic propensities of the mutant αSyn by secondary structure prediction algorithm [24][32][33]. They both raised local (Pα-Pc) values, and the positive-(Pα-Pc) areas coalesced across the loop regions ( Fig 1A, red circles, and 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…To compare influences of hydrophobic amino acids on the local structures of αSyn amyloids, we introduced Met substitution at residues 61 (E61M) and 84 (G84M), where we previously investigated influences of Ile substitutions [24]. We first estimated alteration to intrinsic propensities of the mutant αSyn by secondary structure prediction algorithm [24][32][33]. They both raised local (Pα-Pc) values, and the positive-(Pα-Pc) areas coalesced across the loop regions ( Fig 1A, red circles, and 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…To compare influences of Met and other hydrophobic amino acids on the local structures of αSyn amyloids, we introduced Met substitution at residues 61 (E61M) and 84 (G84M), where we previously investigated influences of isoleucine substitutions [24]. We first estimated intrinsic propensities of the mutant αSyn by secondary structure prediction algorithm [24][32][33]. They both raised local (Pα-Pc) values and the positive-(Pα-Pc) areas coalesced across the loop regions (Fig 1A, red circles, and 1B).…”
Section: Resultsmentioning
confidence: 99%
“…We used the same algorithm (http://cib.cf.ocha.ac.jp/bitool/MIX/) [32] as previously reported [24][33]. To clarify magnitude relations between two of the three conventional parameters, i.e., α-helix propensity (Pα), β-sheet propensity (Pβ), and coil propensity (Pc), we used their arithmetic differences as a new set of parameters, i.e., (Pβ-Pα), (Pβ-Pc) and (Pα-Pc) [24].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the incompatibility between Pick’s Tau amyloid and 4R-Tau substrate by steric conflicts by the Cβ carbon of Val 30 0 demonstrated that strain barriers can be also posed by such local factors. We had hypothesized that conflicts between the local structures of the template amyloid and the corresponding local intrinsic propensity of the substrate peptide can cause a strain barrier, and that the intrinsic propensities are predictable by a secondary structure prediction algorithm [53][54]. Although the algorithm was originally designed for monomeric proteins, the singular structural feature of in-register parallel β-sheet amyloids could allow the application ( Fig 1A ).…”
Section: Insights From MD Simulations Of αSyn Amyloids: Significance mentioning
confidence: 99%
“…Although the algorithm was originally designed for monomeric proteins, the singular structural feature of in-register parallel β-sheet amyloids could allow the application ( Fig 1A ). By comparing the predicted propensities, i.e., β-sheet propensity (Pβ), α-helix propensity (Pα) and coil propensity (Pc), of PrPs from various species, we hypothesized that compatibility of β-arches between PrP Sc and PrP C contributes to species barriers ( Fig 2C ) [54]. Here we test the hypothesis the local conformations and the propensity of substrate with MD simulation, which enables observation of the influences exclusively of the conformations on behaviors of the peptides without any any interference from other factors or proteins.…”
Section: Insights From MD Simulations Of αSyn Amyloids: Significance mentioning
confidence: 99%